STUDY OF MAKING REBON SHRIMP MACARONI (Acetes sp.) BY ADDITION OF CARROT EXTRACT (Daucus carrota) - Shyfa, Resti Nurul; Suparmi, Suparmi; Desmelati, Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThis study aims to obtain the best amount of carrot extract for rebon shrimp macaroni. The research method used was the experiment of making rebon shrimp macaroni with the addition of carrot extract. The research data were analyzed using a one-factor completely randomized design. The test parameters were organoleptic analysis (appearance, aroma, taste and texture), proximate analysis (moisture content, ash content, fat content, protein content and crude fiber content). Research shows that the addition of carrot extract has an effect on the taste of the resulting rebon shrimp macaroni. The use of 300 ml carrot extract concentration is the best treatment with characteristics, namely: it has a slightly thin appearance and is orange in color, the aroma of rebon shrimp is not strong, the taste of rebon shrimp and sweet from carrots, the texture is less dense and brittle. The proximate value of water content is 10.47%, ash content is 1.70%, fat content is 0.62%, protein content is 16.68% and crude fiber content is 0.37%. Keywords: carrots, macaroni, rebon shrimp, taste.